Lichen Planus Induced Poikiloderma - Sayal S K; Gupta C M; Malik A K (Wolters Kluwer Medknow Publications, 2001)
A 32 year old male patient reported initially with lesions of lichen planus. This was followed years later by a network of generalized small erythematous papules, reticulate pigmentation, atrophy and telangiectasia. The histopathological changes were suggestive of lichen planus and poikiloderma.